Physiological and Histopathological Effects of Abetacept (Orencia) Drug on Liver of Albino Male Mice - Hussein Ali, Dina Khudhair (Iraqi Journal of Science, 2023)
A study investigated the effects of abetacept (Orencia) drug on the level of liver enzyme and on liver histology in albino male mice. Fourty five adult male mice of 8 weeks age and weighting 25-35g divided into three groups (15 mice each). The second & third groups were treated with abetacept drug while the first group was used as a control.Abetacept was intraperitoneally given twice every week at 125 mg/kg B.W. and 250 mg/kg B.W. to the second and third groups respectively for 6 weeks, whereas the control group was intraperitoneally injected with normal saline. The results showed a significant (p< 0.05) increase in the levels of liver enzymes [serum alanine aminotransaminase (ALT), serum aspartate aminotransaminase (AST) & alkaline phosphatase (ALP)] compared to control group. Also there was a significant (p< 0.05) increase in the level of these enzymes in the third group compared to the second group. Some histopathological changes were found in liver of treated mice with this drug represented in ; hyperplasia of bile ducts epithelial lining cells and fibrosis in portal area of bile ducts, infiltration of neutrophile and mononuclear cell in the lumen of dilated sinusoids and central vein, necrotic area of hepatocytes and hyper atrophy of proliferated kupffer cells.The results of this study concluded that the treatment with abetacept caused increased in the level of liver enzymes and damage in its tissues.